Evolution of positive cases and deaths from Covid-19 in Peru, and the f factor through a physical model - Merma, Marco (2022)
In the context of the spread of the coronavirus (Covid-19), worldwide, data has been reported on the number of positive cases, deaths, hospitalized, recovered, etc. In the case of Peru by the Ministry of Health (MINSA), from these an analysis is carried out, emphasizing the number of positive cases and deaths and taking as reference the behavior of a physical phenomenon, a number f is postulated, to describe the evolution of positive cases and deaths from coronavirus.